Screening of Compounds for Anti-tuberculosis Activity, and in vitro and in vivo Evaluation of Potential Candidates - Zhou, Wei; Yang, Bing; Zou, Yanyan; Rahman, Khaista; Cao, Xiaojian; Lei, Yingying; Lai, Ren; Fu, Zhen F.; Chen, Xi; Cao, Gang (Frontiers in Microbiology, 2021)
Tuberculosis (TB) is a debilitating infectious disease responsible for more than one million deaths per year. The emergence of drug-resistant TB poses an urgent need for the development of new anti-TB drugs. In this study, we screened a library of over 4000 small molecules and found orbifloxacin and the peptide AK15 possess significant bactericidal activity against Mycobacterium tuberculosis (Mtb) in vitro. Orbifloxacin also showed an effective ability on the clearance of intracellular Mtb and protect mice from a strong inflammatory response but not AK15. Moreover, we identified 17 nucleotide mutations responsible for orbifloxacin resistance by whole-genome sequencing. A critical point mutation (D94G) of the DNA gyrase (gyrA) gene was found to be the key role of resistance to orbifloxacin. The computational docking revealed that GyrA D94G point mutation can disrupt the orbifloxacin-protein gyrase interactions mediated by magnesium ion bridge. Overall, this study indicated the potential ability of orbifloxacin as an anti-tuberculosis drug, which can be used either alone or in combination with first-line antibiotics to achieve more effective therapy on TB.